Eliciting chefs’ creativity in utilising Malaysian local herbs in the development of modern Malaysian cuisine - Zainal Abidin, Muhammad Rezza (2023)
Since 2011, herbal trade has become a new source of economic growth in Malaysia, coinciding with the increase in global demand for herbal products. However, despite its significance, minimal emphasis has been paid to the use of herbs in culinary practices, particularly in creative and innovative culinary creations development. Most of the existing creativity literature explored how creativity enables chefs to survive in a fast-paced industry. However, there are still substantial misunderstandings about how creative culinary processes unfold. Because of that, the rising trend of modernist cuisine may be a platform to unravel this phenomenon, as it requires a higher level of chefs’ creativity to interpret it. Thus, this study investigates the utilisation of Malaysian local herbs (MLH) in modern cuisine development and illuminates chefs’ creativity in contemplating the creation of modern Malaysian cuisine (MMC). This study aimed to develop a framework that dynamically conceptualises creative culinary processes by analysing chefs’ creativity in fusing local produce into modern products through an inductive qualitative approach, using a multiple-case study design. Twenty-three informants were involved in this study: reputable modern chefs, food and industrial experts, culinary and food service academicians, and local government authorities. The data were primarily gathered through semi-structured in-depth interviews, participatory observations, interviews with related resources, and focus group discussions to best depict the repertoire and nuances of the creative culinary process of utilising MLH in the creation of MMC. The data was organised and analysed in two phases using the constant comparison analysis: the first phase was to capture the individual dynamic lens of each chef’s creative thought process, while the second phase was to analyse and group each informant’s lens into categories that best encapsulate the creative culinary process in the creation of MMC. This was then followed by the cross-case analysis to seek convergent and divergent data across cases and solidify the categories into four unique themes: (1) embodiment of knowledge, (2) challenges of modernising the “orthodox”, (3) acclimatisation of modern cooking techniques and modern technology equipment, and lastly (4) conceptualisation of creativity in MMC. In essence, this study contributes to three facets. First, it provides empirical evidence that creativity is intentional rather than accidental. It implies that the creative culinary process can be dynamically schematised as a motivating and essential aspect of human life that yields emotional and gratifying rewards for the creator. Second, the integrated creative culinary process model provides a set of steps that can be used to generate ideas and then transform them into creative innovations. It also contributes to the body of knowledge by indicating that such a sequence is a dynamic flow that generates more profound ways for chefs to articulate their creative thought processes. Finally, this study sheds new light on the dynamics that allow the equilibrium between familiarity and novelty in agricultural and creative industries, where products suffer from significant inattention, by revealing the key challenge of developing a modern cultural product that differs deeply from the traditional ones. In so doing, this study focused on the product level by investigating the main fusing strategies to balance novelty and familiarity. While previous works have mainly underlined the importance of using traditional knowledge to create new products, this study specified the usefulness of new combinations between traditional and cultural elements with modern elements since existing literature has claimed the perils of offshoring for the recombinant of cultural and artistic cuisine innovations.